Exploring the Multifaceted Relationships Between Mindful Parenting, Family Relationships, and Mothers' Reflective Functioning with the Emotional Social Adaptation of Children with Autism - Alhammashi, Alaa Najm Abed; Yousefi, Zahra; Radhi, Abboud Jawad; Khayatan, Floor (Health Nexus, 2024)
This study aimed to investigate the multifaceted relationships between mindful parenting, family relationships, and mothers' reflective functioning with the emotional social adaptation of children with autism. The research was descriptive and correlational. The population consisted of all mothers with autistic children in the city of Kut. The sample included 200 mothers of children with autism, selected through convenience sampling. The research instruments were: the Children's Social Skills Questionnaire (Payton, 2008), Reflective Functioning (Yousefi, 2023), Mindful Parenting (McCaffrey, 2017), and Family Relationships by Barnes and Olson (1987). For data analysis, descriptive statistics (mean and standard deviation) and inferential statistics (Pearson correlation coefficient and stepwise regression) were used. The results showed that among the predictor variables, mindful parenting and its dimensions, relationship with spouse, and balanced reflective functioning had a significant relationship with the emotional social adaptation of children with autism. Among the mentioned variables, mindful parenting, relationship with spouse, and acceptance of the child had predictive power for emotional social adaptation. Based on these results, it can be said that improving the variables of parenting is beneficial for enhancing the emotional social adaptation of children.